Pengaruh Pelanggaran Perjanjian, Leverage, dan Financial Distress terhadap Audit Delay - Natalis Christian; Helvida Githa Putri Br Purba (Journal of Trends Economics and Accounting Research, 2023)
The delays in submitting audit reports in Indonesia are increasing every year. This increase could be caused by several variables. In light of these problems, this study aims to determine the effect of breach of agreement, financial leverage and financial distress on audit delay. Using secondary data, the sample used comes from companies listed on the Indonesia Stock Exchange with a time period of 2017-2021. Test sample data using Eviews with regression panel. The results of this study indicate that breach of the agreement and financial hardship have an effect on delaying the review with a probability value of 0.0001 and 0.0134 and financial leverage has a negative effect on delaying the review with a probability value of 0.0137. This research is expected to present theoretical implications in the form of adding new theories related to audit delays and administrative implications for firms to be able to manage their debts to reduce the submission of lengthy audit reports.